Stress and psychological well being status among health care professionals - Halder, Susmita; Mahato, Akash Kumar (International Journal of Occupational Safety and Health, 2013)
Stress is a condition or feeling experienced when a person perceives that “demands exceed the personal and social resources the individual is able to mobilize” (Lazarus)1. It could be debatable whether stress is inevitable, but most professionals report stress at work place and in general. A common perception prevails regarding high stress level amongst professionals in particular industries like the information technology, professionals with fieldwork (medical representatives, insurance agents) that is also backed by study findings. However, stress among health care professionals is less explored. The present study aims to explore and assess psychological well being and stress levels among health care professionals. 50 health professionals, including doctors, paramedical and nursing staffs from different multi-specialty hospitals in Kolkata were assessed on the General Health Questionnaire (GHQ 12) and the Professional Life Stress scale, and Medico Psychological Questionnaire. Majority of the subjects had evidence of psychological distress. Stress level was present in varying degree among all professionals, while nurses and technicians had stress level at severe level. DOI: http://dx.doi.org/10.3126/ijosh.v3i1.9099 International Journal of Occupational Safety and Health, Vol 3 No 1 (2013) 32-35